Professional Social Workers in the Era of Revolution 4.0 (Case Study in Medan ODH Social Rehabilitation Center) - Agussani Agussani; Emilda Sulasmi (Islam Realitas: Journal of Islamic and Social Studies, 2021)
Abstract This article aims to explain the challenge professional social workers in order to empower the community based on their license. The method used in this study is qualitative method with the study in ODH Social Rehabilitation Center "Bahagia" Medan. This article found that the challenge of professionalism of technology-based social workers is internally related to using digital communication facilities. This can be overcome by training and mentoring and making technological innovations to strengthen social work in community empowerment. This article contributes the necessary knowledge that social workers must be civilized with information technology in today's digital age to support social workers' professionalism by using a dualistic approach in industrial revolution 4.0 towards the Society 5.0 revolution. Regarding the Certificate, it was found that certification is relevant to the professionalism of Social workers in Indonesia, especially social workers in the Center for The Development of Functional Positions of Social Workers and Social Extension, The Ministry of Social Affairs, and the Social Rehabilitation Center ODH "Bahagia" Medan.AbstrakArtikel ini bertujuan untuk menjelaskan tantangan pekerja sosial profesional dalam rangka melakukan pemberdayaan masyarakat berdasarkan lisensi yang dimiliki. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan studi pada Balai Rehabilitasi Sosial ODH “Bahagia” Medan. Artikel ini menemukan bahwa bentuk tantangan profesionalisme pekerja sosial berbasis teknologi adalah secara internal berkenaan dengan kemampuan pemanfaatan sarana komunikasi digital, ini dapat diatasi dengan pelatihan dan pendampingan serta melakukan inovasi teknologi guna memperkuat kerja sosial dalam rangka pemberdayaan masyarakat. Artikel ini memberi kontribusi pengetahuan penting bahwa ternyata pekerja sosial harus beradabtasi dengan teknologi informasi di era digital saat ini, guna mendukung profesionalisme pekerja sosial dengan menggunakan dualistic approach pada era revolusi industri 4.0 menuju revolusi Society 5.0. Mengenai Sertifikat, ditemukan bahwa terdapat relevansi sertifikasi dengan profesionalisme pekerja Sosial di Indonesia, khususnya pekerja sosial di Pusat Pembinaan Jabatan Fungsional Pekerja Sosial dan Penyuluh Sosial, Kementerian Sosial dan Balai Rehabilitasi Sosial ODH “Bahagia” Medan.